Analysis of the Purchasing Decision-Making Process in E-Commerce Using Sed Method from Neuromarketing - Cifuentes-Alfaro, F (Elsevier B.V., 2022)
The important global advance in digital transformation, together with the effects of the pandemic experienced worldwide, have allowed a great growth of electronic commerce (e-commerce), providing people with various benefits such as greater convenience in the purchase of products and/or services, the experience of quoting in different types of retail stores, choosing payment methods and opting for timely deliveries. Companies and entrepreneurs, for their part, have had the opportunity to exhibit and offer their products/services digitally, achieving a great impact on sales. This work analyzes the behavior of a group of consumers in decision-making processes for e-commerce purchase, using Neuro marketing tools and techniques, considering certain learning styles present in the process. The methodology used is mixed and exploratory, qualitative and quantitative, using non-traditional Neuro-marketing tools such as EEG, supported by traditional surveys. The results obtained show that, regardless of gender, the person is constantly making decisions, since the frontal lobe was the one that presented the greatest brain activity in almost all cases, associated with behavioral control, planning, attention and thought. However, sometimes the final purchase decision did not always refer to the consumer s unconscious, but in some other times it was triggered by the influence of factors such as price, means of payment and/or promotions. This was reflected in the stage of evaluation of alternatives, through the activation of the right prefrontal lobe in a device different from the one finally chosen. An interview conducted at the end of the experiment allowed to validate the result from the electroencephalography. © 2022 The Author(s).